Shopping Through Social Media: A Study On Consumer Behavior In Facebook’s Online Shop Page - Albert, Albert (2015)
Nowadays, social media like Facebook and Twitter, showed increasing number rapidly from time to time. In Indonesia, Facebook has become the largest social media, being the second place in user number, comparing to other countries. As a result, one of the aspects that affected by this social media phenomena is business. The development of social media provides a developing prospect for E-marketers and digital enterpreneurs. If E-marketers know the insights on their buyers’ characteristic, they could get insights on how customers interpret and receive stimuli (messages/informations), which could affect customers’ decisions.